Aqueous zinc ion battery and electrolyte thereof
By adding sodium quaternary anion additives of NaCl, NaF, NaBr and NaI to the electrolyte of aqueous zinc ion batteries, adjusting their component ratio and zinc salt concentration to form a stable hydrogen bond network, solving the performance problems of the battery at ultra-low and high temperatures, and achieving stable operation under ultra-wide temperature domain and long cycle conditions.
Patent Information
- Application Number
- CN202411876700.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The electrolyte of existing aqueous zinc ion batteries has poor performance at ultra-low temperatures and high temperatures, making it difficult to take into account the application requirements of low temperatures and high temperatures, and is poor in stability during long cycles.
An electrolyte containing sodium quaternary anion additives containing NaCl, NaF, NaBr and NaI is used to form a stable hydrogen bond network by adjusting the component ratio of the additive and the concentration of zinc salt, which inhibits the activity of water and improves the migration performance of zinc ions.
The ultra-wide temperature domain and long cycle performance of aqueous zinc ion batteries are significantly improved, and can operate stably at low temperatures of -40°C and high temperatures of 80°C, and maintain excellent stability during long cycles.
Smart Images

Figure CN119742467A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zinc ion batteries, and in particular relates to the field of electrolytes of zinc ion batteries. Background Art
[0002] Aqueous zinc-ion batteries are aqueous solutions, and the more common electrolytes are zinc salt aqueous solutions, where zinc salts mainly include zinc chloride, sulfuric acid, Zn(CF3SO3)2, Zn(CH3F3SO3)2, Zn(CH3COO)2, etc. The concentration of zinc salts is generally 0.5~5M. However, the performance of this conventional electrolyte is not ideal. To address this issue, the mainstream idea in the industry is to add various additives to the electrolyte to improve its different properties.
[0003] For example, the Chinese patent document with publication number CN112510178A discloses a seawater-based electrolyte, which is an aqueous solvent in which zinc salt and additives are dissolved, wherein the additive is a mixture of one or more of MnSO4, Mn(CF3SO3)2, MgCl2, MgSO4, NaCl, and Na2SO4; the molar ratio of the additive to the zinc salt is 2:1 to 1:10. For another example, the Chinese patent document with publication number CN114824263A discloses a Zn@Zn-E composite negative electrode, its preparation, and its application in aqueous zinc ion batteries, specifically disclosing an electrolyte of an aqueous solution in which zinc salt, a compound containing a non-metallic element E, a complexing agent, a conductive salt, a grain refiner, and an anode activator are dissolved.
[0004] In summary, although there are many reports of electrolytes modified by additives in the prior art, and some additive solutions claim to improve their low-temperature performance, most of them can only improve their low-temperature performance of -10°C, and it is difficult to further improve their ultra-low temperature performance (such as -40°C). In addition, aqueous electrolytes are prone to gasification at high temperatures, especially at temperatures above 60°C, and their high-temperature performance is not ideal, making it difficult to take into account both low-temperature and high-temperature application requirements. In other words, existing aqueous zinc-ion batteries are still difficult to adapt to the application requirements of ultra-wide temperature range and long cycle. Summary of the invention
[0005] In view of the problems faced by aqueous zinc ion batteries, the first object of the present invention is to provide an electrolyte for an aqueous zinc ion battery, aiming to improve its low-temperature, high-temperature and long-cycle stability.
[0006] A second object of the present invention is to provide an aqueous zinc ion battery comprising the electrolyte.
[0007] The invention discloses an electrolyte for an aqueous zinc ion battery, which is an aqueous solution in which zinc salt and additives are dissolved. The additives include NaCl, NaF, NaBr and NaI.
[0008] The present invention innovatively combines the sodium-type quaternary anion additive, which can effectively stabilize the hydrogen bond network of water to inhibit the activity of water, and can deeply optimize its ultra-low temperature performance. In addition, it can also effectively inhibit high-temperature gas production and improve high-temperature performance. The electrolyte described in the present invention can significantly improve the ultra-wide temperature range performance and long cycle performance of aqueous zinc-ion batteries.
[0009] In the present invention, the zinc salt may be a water-soluble zinc salt known in the industry, such as one or more of zinc sulfate, zinc trifluoromethanesulfonate, bistrifluoromethanesulfonyl zinc Zn(TFSI)2, and zinc acetate Zn(CH3COO)2.
[0010] In the present invention, the concentration of zinc salt is 0.5-2 M, preferably 0.5-1 M, and further 0.7-0.9 M. In order to reduce the activity of water, the prior art mostly needs to rely on high zinc ion concentration to achieve it. However, the research of the present invention shows that the combination of the additive components can unexpectedly improve the ultra-wide temperature range performance and long cycle performance of the prepared electrolyte at low zinc ion concentration.
[0011] The present invention also shows that the combined control of the proportion of the additive ingredients can help further adjust the activity of water and help further improve the ultra-wide temperature range performance and long cycle performance of aqueous zinc-ion batteries.
[0012] In the present invention, in the additive, the molar ratio of NaF, NaCl, NaBr, and NaI is 0.05-0.15: 0.05-0.15: 0.02-0.06: 0.02-0.06; preferably 0.08-0.12: 0.07-0.09: 0.04-0.05: 0.03-0.05; more preferably 0.9-0.1: 0.07-0.08: 0.045-0.05: 0.04-0.045. Studies have shown that under the preferred ratio, better component synergy can be obtained, and better ultra-wide temperature stability and stability can be obtained.
[0013] In the present invention, in the additive, the molar amount of NaF is preferably 33-38%, the molar amount of NaCl is preferably 30-32%, the molar amount of NaBr is 15-20%, and the balance is NaI.
[0014] Preferably, the total concentration of the additive is 20-55% of the molar amount of the zinc salt anion, preferably 20-40%, and more preferably 30-35%. Studies have shown that under the preferred additive ratio, better component synergy, better ultra-wide temperature stability and stability can be obtained.
[0015] The present invention also provides an aqueous zinc ion battery, comprising a battery core which is sequentially composited with a positive electrode, a diaphragm and a negative electrode, and an electrolyte for soaking the battery core, wherein the electrolyte is the electrolyte described in the present invention.
[0016] The washed zinc ion battery of the present invention, in addition to the electrolyte of the present invention, other components such as the positive electrode, the negative electrode and the separator can be components known in the industry, or can be obtained by adjusting based on known means.
[0017] The positive electrode comprises a current collector and a positive electrode material composited on the surface thereof. The active material in the positive electrode material may include at least one of manganese dioxide, vanadium pentoxide, ammonium vanadate, sodium vanadium phosphate, and sodium iron pyrophosphate.
[0018] The negative electrode may be, for example, zinc metal.
[0019] The separator may be, for example, a cellulose separator having a thickness of 20 to 600 μm.
[0020] Beneficial Effects The present invention innovatively combines the sodium-type quaternary anion additive to effectively inhibit the activity of water by forming a stable hydrogen bond network, and promote the uniform and rapid migration of zinc ions, which can deeply optimize its ultra-low temperature performance. In addition, it can also effectively inhibit high-temperature gas production and improve high-temperature performance. The electrolyte described in the present invention can significantly improve the ultra-wide temperature range performance and long cycle performance of aqueous zinc-ion batteries.
[0021] The research of the present invention shows that the electrolyte can be adapted to low-temperature applications of -40°C and high-temperature applications of 80°C, and can be adapted to ultra-wide temperature range application requirements. In addition, it can also take into account excellent long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Symmetrical cells of Example 1 and Comparative Example 1 at 25°C, 5 mA / cm 2 and 5mAh / cm 2 Electrochemical performance under Figure 2 Symmetrical cells of Example 1 and Comparative Example 1 at -40°C, 1 mA / cm 2 and 1mAh / cm 2 Electrochemical performance under Figure 3 Symmetrical cells of Example 1 and Comparative Example 1 at 80°C, 1 mA / cm 2 and 1mAh / cm 2 Electrochemical performance under Figure 4 The electrochemical performance of the full batteries of Example 1 and Comparative Example 1 at 25°C. DETAILED DESCRIPTION
[0023] Example 1
[0024] The electrolyte is an aqueous solution containing zinc sulfate and an additive, wherein the concentration of zinc sulfate is 0.8M; The additives are NaF, NaCl, NaBr and NaI, and their concentrations are 0.096M, 0.08M, 0.048M and 0.04M, respectively.
[0025] test: (1): Half-cell: The zinc sheet and electrolyte were assembled into a symmetrical battery, with a cycle life of 2500 h at 25°C, 5 mA / cm2 and 5 mAh / cm2, a cycle life of 1000 h at -40°C, 1 mA / cm2 and 1 mAh / cm2, and a cycle life of 2000 h at 80°C, 1 mA / cm2 and 1 mAh / cm2.
[0026] (2): Full battery: Positive electrode: V2O5, conductive agent (conductive carbon black), and binder PVDF are compounded on the current collector in a weight ratio of 7:2:1 to form a positive electrode, and the positive electrode, separator, zinc negative electrode, and the above-mentioned electrolyte are compounded to form an aqueous zinc ion battery.
[0027] At a current density of 1A / g and a temperature of 25°C, the battery was cycled for 910 cycles (the number of cycles required for the capacity to decay to 40%).
[0028] Example 2 Compared with Example 1, the only difference is that the concentration of zinc sulfate in the electrolyte is 0.5 M, and other operations, parameters and tests are the same as those in Example 1.
[0029] Symmetrical battery performance: Its cycle life is 2331h at 25℃, 5mA / cm2 and 5mAh / cm2, 810h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1612h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0030] Full battery performance: 821 cycles at 25°C.
[0031] Example 3 Compared with Example 1, the only difference is that the concentration of zinc sulfate in the electrolyte is 1.5 M, and other operations, parameters and tests are the same as those in Example 1.
[0032] Symmetrical battery performance: Its cycle life is 1922h at 25℃, 5mA / cm2 and 5mAh / cm2, 631h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1485h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0033] Full battery performance: Full battery life is 740 weeks.
[0034] It can be seen from Examples 1 to 3 that the additive of the present invention is used to control the zinc salt concentration below 1 M, especially to 0.7 to 0.9 M, which helps to obtain better ultra-low temperature and ultra-high temperature performance, and can also obtain better long-cycle stability.
[0035] Example 4 Compared with Example 1, the only difference is that zinc trifluoromethanesulfonate is used as the zinc salt, and other operations, parameters and tests are the same as those in Example 1.
[0036] Symmetrical battery performance: Its cycle life is 2430h at 25℃, 5mA / cm2 and 5mAh / cm2, 923h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1705h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0037] Full Cell Performance: The full cell life of this electrolyte with V2O5 and zinc sheet assembly is 850 weeks.
[0038] Example 5
[0039] Compared with Example 1, the only difference is that in the electrolyte, the molar concentrations of the additives NaF, NaCl, NaBr and NaI are 0.08M, 0.07M, 0.04M and 0.04M respectively.
[0040] Symmetrical battery performance: The zinc sheet and electrolyte were assembled into a symmetrical battery, with a cycle life of 2213 h at 25°C, 5 mA / cm2 and 5 mAh / cm2, 675 h at -40°C, 1 mA / cm2 and 1 mAh / cm2, and 1560 h at 80°C, 1 mA / cm2 and 1 mAh / cm2.
[0041] Full battery performance: Full battery life is 671 weeks.
[0042] Example 6 Compared with Example 1, the only difference is that the molar ratio of the additives is changed, specifically: NaCl, NaF, NaBr and NaI, the concentrations of which are 0.096 M, 0.08 M, 0.048 M and 0.04 M respectively. The total molar amount of the additives is the same as that of Example 1.
[0043] (1): Half-cell: The cycle life is 2426h at 25℃, 5mA / cm2 and 5mAh / cm2, 932h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1854h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0044] (2): Full battery: The battery was cycled for 812 cycles at a current density of 1 A / g and a temperature of 25°C.
[0045] Comparative Example 1 Compared with Example 1, the only difference is that the electrolyte is a 0.8M zinc sulfate solution without any additives, and the other operations, operations and tests are the same as those in Example 1.
[0046] Symmetrical battery performance: Its cycle life is 110h at 25℃, 5mA / cm2 and 5mAh / cm2, and 95h at -40℃, 1mA / cm2 and 1mAh / cm2. It initially decomposes at 80℃, 1mA / cm2 and 1mAh / cm2, and fails after 50 hours of cycling.
[0047] Full battery performance: The full battery fails after 200 cycles.
[0048] Comparative Example 2 Compared with Example 1, the difference is that the additive only contains sodium chloride, and the total concentration of the additive and other operations are the same as Example 1.
[0049] Symmetrical battery performance: Its cycle life is 1203h at 25℃, 5mA / cm2 and 5mAh / cm2, 350h at -40℃, 1mA / cm2 and 1mAh / cm2, and 965h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0050] Full battery performance: 482 full battery cycles.
[0051] Comparative Example 3: Compared with Example 1, the difference is that the additive only contains sodium chloride and sodium fluoride (the molar ratio of the two is the same as that of Example 1), and the total concentration of the additive and other operations are the same as those of Example 1.
[0052] Symmetrical battery performance: Its cycle life is 1380h at 25℃, 5mA / cm2 and 5mAh / cm2, 442h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1020h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0053] Full battery performance: Full battery cycle 510 weeks.
[0054] Comparative Example 4: Compared with Example 1, the difference is that the additive only contains sodium chloride, sodium fluoride, and sodium iodide (the molar ratio of the three is the same as that of Example 1), and the total concentration of the additive and other operations are the same as those of Example 1.
[0055] Symmetrical battery performance: Its cycle life is 1575h at 25℃, 5mA / cm2 and 5mAh / cm2, 483h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1162h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0056] Full battery performance: 581 full battery cycles.
[0057] Comparative Example 5: Compared with Example 1, the difference is that the sodium element in the additive is replaced by Zn, and the total concentration of anions in the additive and other operations are the same as in Example 1.
[0058] Symmetrical battery performance: Its cycle life is 1720h at 25℃, 5mA / cm2 and 5mAh / cm2, 505h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1284h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0059] Full battery performance: Full battery cycle 613 weeks.
[0060] Comparative Example 6: Compared with Example 1, the difference is that the sodium element in the additive is replaced by magnesium, and the total anion concentration of the additive and other operations are the same as in Example 1.
[0061] Symmetrical battery performance: Its cycle life is 1810h at 25℃, 5mA / cm2 and 5mAh / cm2, 512h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1244h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0062] Full battery performance: 635 full battery cycles.
[0063] Comparative Example 7: Compared with Example 1, the difference is that the sodium element in the additive is replaced by ammonium ions, and the total anion concentration of the additive and other operations are the same as in Example 1.
[0064] Symmetrical battery performance: Its cycle life is 1870h at 25℃, 5mA / cm2 and 5mAh / cm2, 553h at -40℃, 1mA / cm2 and 1mAh / cm2, and 1345h at 80℃, 1mA / cm2 and 1mAh / cm2.
[0065] Full battery performance: 668 full battery cycles.
Claims
1. An electrolyte for an aqueous zinc ion battery, which is an aqueous solution in which a zinc salt and an additive are dissolved, characterized in that: The additives include NaCl, NaF, NaBr and NaI.
2. The electrolyte of the aqueous zinc ion battery according to claim 1, wherein The zinc salt includes one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl) Zn(TFSI)2, and zinc acetate Zn(CH3COO)2.
3. The electrolyte of the aqueous zinc ion battery according to claim 1 or 2, wherein The concentration of the zinc salt is 0.5-2M, preferably 0.5-1M; more preferably 0.7-0.9M.
4. The electrolyte of the aqueous zinc ion battery according to claim 1, wherein In the additive, the molar ratio of NaF, NaCl, NaBr and NaI is 0.05-0.15: 0.05-0.15: 0.02-0.06: 0.02-0.
06.
5. The electrolyte of the aqueous zinc ion battery according to claim 4, characterized in that In the additive, the molar ratio of NaF, NaCl, NaBr and NaI is 0.08-0.12: 0.07-0.09: 0.04-0.05: 0.03-0.05; more preferably, it is 0.9-0.1: 0.07-0.08: 0.045-0.05: 0.04-0.
045.
6. The electrolyte of the aqueous zinc ion battery according to claim 1, 4 or 5, characterized in that: The total concentration of the additive is 20-55% of the molar amount of the zinc salt anion, preferably 20-40%, and more preferably 30-35%.
7. An aqueous zinc ion battery, comprising a battery cell which is sequentially combined with a positive electrode, a separator and a negative electrode, and an electrolyte for soaking the battery cell, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 6.
8. The aqueous zinc ion battery according to claim 7, characterized in that: The positive electrode comprises a current collector and a positive electrode material composited on the surface of the current collector. The active material in the positive electrode material comprises at least one of manganese dioxide, vanadium pentoxide, ammonium vanadate, sodium vanadium phosphate and sodium iron pyrophosphate.
9. The aqueous zinc ion battery according to claim 7, wherein: The negative electrode is a zinc metal negative electrode.
10. The aqueous zinc ion battery according to claim 7, characterized in that: The separator is a cellulose separator with a thickness of 20-600 μm.
Citation Information
Patent Citations
Three-dimensional alloy negative electrode material and application thereof in preparation of secondary energy storage battery
CN112510178A
Zn-coated Zn-E composite negative electrode, preparation thereof and application of Zn-coated Zn-E composite negative electrode in aqueous zinc ion battery
CN114824263A
Aqueous zinc ion battery and electrolyte thereof
CN116544530A
Electrolyte, battery and electric equipment
CN118248940A
Aqueous metal battery electrolyte and application thereof
CN118248968A
Cited By
Aqueous zinc ion battery electrolyte, preparation method thereof and zinc ion battery
CN121260957A
Aqueous zinc ion battery electrolyte and preparation method thereof, zinc ion battery
CN121260957B